Bioconcentration of Lead at Avicennia Marina in Mangunharjo, Semarang Coastal Area - Zallva Arsyta Hartanto; Agus Hartoko; Haeruddin Haeruddin (Politeknik Kelautan dan Perikanan Dumai, 2022)
This study aims to determine the bioconcentration of heavy metal Lead Pb in seawater, sediment, and mangrove plants of Avicennia marina and to determine the bioconcentration factor of heavy metal Lead Pb in mangrove which was conducted in January 2022 in Mangunharjo coastal area. The method used in this research was a survey method with quantitative analysis. The samples of A. marina mangroves were divided into three categories of stem diameter, namely small (3 – 8 cm), medium (6 – 15 cm), and large (11 – 23 cm). Measurement of heavy metal concentrations using AAS (Atomic Absroption Spectrophotometry). Heavy metal bioconsentration in Mangunharjo is classified as high exceeding quality standards. The study revealed that the concentration of heavy metal Lead Pb in the seawater ranged from 0.672 - 0.867 mg/L, in sediments it ranged from 56.50 – 65.96 mg/kg, and in the roots and leaves of mangroves A. marina ranged from 6.209 – 24,883 mg/kg. The bioconcentration factor of heavy metal Lead Pb ranges from 0.185 to 0.227, so that the mangrove A. marina in Mangunharjo Water Area can be classified as an excluder species.